An investigation into loss and gain in the Vietnamese translational equivalents of english idioms used in the 4 th volume of the novel series “harry potter” by j.k. rowling - Võ Thị Diệu Linh (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
Idioms are an integral part of language which contributed to the success of the 4th Volume of the HP novel and play an important role in defining the writing style of the British author J.K.Rowling. Thanks to their unique features in semantic and structure aspects, idioms enable the language users to express their idea, attitude and emotions in concise and interesting ways. The aim of this study is to identify the English idioms used in the 4th Volume of the HP novel and examine the loss and gain phenomena in terms of lexis, structure and meaning in their Vietnamese translational equivalents. In the light of Baker’s theory of idiom and the translation theory of Newmark, the data of the study were collected, described and analyzed under qualitative and quantitative approaches in order to discover the loss and gain phenomena. Based on the translation shifts theory of Catford, 197 samples of loss and gain were examined to identify occurrences of translation shifts. Due to the differences of language and culture as well as the specific features or idioms, the loss and gain phenomena seem to be unavoidable in the translation of the idioms in the 4th Volume. This thesis was carried out to point out and analyze these phenomena with the hope of making a minor contribution to the teaching and learning of idioms, especially to English-Vietnamese translation.